Monitoring of yellow rust (Puccinia striiformis f.sp. tritici) of wheat in the Almaty region conducted in 2019–2021 - Keishilov, Zh.S.; Kokhmetova, А.М.; Kumarbayeva, М.Т.; Zhanuzak, D.K.; Rsaliyev, Sh.S. (Fundamental and Experimental Biology, 2022)
Yellow rust (P. striiformis f.sp.tritici) is an important disease of wheat (Triticum aestivum), especially in cool and moist weather conditions. In Central Asian countries, including Kazakhstan, yellow rust remains a serious disease in wheat crop area. In our research2019–2020 in the Almaty region in Zhambyl, Karasai, Talgar regions, cultivars were selected, that have high resistance to the P. striiformispathogen, which showed the immune type of reaction “IT — 0: Vassa”, “Naz”,“Bezostaya-1”, “Sapaly”, and “Triticale”. At the same time, based on the data of phytopothological monitoring, in the Zhambyl region, the greatest spread of the disease was observed in the cultivar “Bogarnaya 56”,the prevalence was 26%, and the level of infestation was 9.90%. In the Talgar region, in the winter wheat cultivar “Kazakhstan–10”, the prevalence of yellow rust disease was 6%, and the level of infection was 0.52%. In the Karasai region, the cultivar “Karasai” was found to have a high level of yellow rust infestation, the prevalence of the disease was 22%, and the infestation was 1.04%. In addition, as a result of the monitoring carried out in 2021, the obtained data demonstrated that all the studied wheat cultivars were resistant to the P. striiformis pathogen due to dry weather and lack of precipitation, low humidity resistance to the disease was high. Research shows the need for continued work to find new sources of yellow rust resistance. The results of the experiment show that most of the wheat varieties in the Almaty region are not resistant torust diseases.